PENGARUH STRES KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP TURNOVER INTENTION KARAYAWAN PT.KREASI EDULAB INDONESIA - Lubis, Fauzan Dwi Putra; Rodhiyah, Rodhiyah (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2017)
The high turnover rate is a major problem in the company. The factor of turnover intention are work stres and leadership style. Prupose of this research are is know how much the influence of Job Stres and Transformational Leadership Style on Turnover Intention PT. Kreasi Edulab Indonesia employees. type of research is explanatory with a population of 129, the sample of respondents are permanent and contract employees as many as 57 people. Using stratified random sampling technique. Analysis using correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, t test, F test and classical assumption with SPSS. Results and discussion, the majority of work stres levels is low but there is still a high work stres due to lack of pay and rewards, transformational leadership style is suitable but there are respondents were not suitable because of the lack of attention and turnover intention in the company's is high. Correlation of job stres is 0.324 and have weak cohesion. The regression equation for the stres work is Y = 8.923+0,497X1 and determination coefficient of 10.5%. t test is t count 2,540 > t table 2,004. There is a positive and significant influence between Work Stres on Turnover Intention partially. Correlation for Transformational Leadership Style is 0,243 and have a weak cohesion. T test is 1,861 t count < t table 2,004. There was no relationship between Transformational Leadership Style on Turnover Intention partially. Conclusions and suggestions, a multiple regression equation Y = 7.282 + 0,414X1 +0,145X2 and the coefficient of determination variables is 11.4%. t test for variables simultaneously are 3.458 F count > F table 3,17 and free of classical assumptions. there were positive and significant relationship between both independent variables on turnover intention. Suggestions for the company are prioritizing the rights of employees, socialization of reward and punishment policies and better communications to the employees.